Laju Pertumbuhan, Biomassa, dan Produksi Fikosianin Arthrospira platensis Perairan Pulau Jawa Pada Variasi Salinitas - Lestari, Mutia Dinda; Sajidan; Pangastuti, Artini (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify and determine the optimal salinity that can produce specific growth rates, maximum dry biomass production, and the highest phycocyanin content and productivity in local strains of A. platensis in the waters of Java Island. This study was conducted using three strains of Arthrospira platensis originating from Jepara, Bogor, and Yogyakarta with salinity variations of 10, 20, and 30 ppt and three replicates using walne fertilizer culture media. The cultures were cultivated for eight days to calculate the growth rate and measure the biomass and phycocyanin concentration. The results of this study showed that the biomass of A. platensis in all strains was maximum at 30 ppt. The specific growth rate of A. platensis strains JPR and BGR was fastest at 30 ppt, and phycocyanin production was highest at 20 ppt. Meanwhile, the MRP strain showed a fast growth rate at 10 ppt and the highest phycocyanin production at 30 ppt. Based on the results of this study, it can be concluded that each strain has a different strategy in responding to salinity in terms of growth rate, biomass, and phycocyanin production.